Student Perspectives in Viewing Gender Non-Conformities - Abid Firdaus, Faathir; Maulana, Arif Rahman; Maharani, Nabila; Arinta Aulia, Rasya (Jurnal Polisci, 2025)
This research addresses the issue of Gender Non-Conformities (GNC) in the social and legal context in Indonesia, focusing on the freedom of individuals to express their gender identity and the challenges faced related to cultural and religious norms. Gender non-conformity refers to individuals whose gender expression does not conform to social expectations of masculinity or femininity. In Indonesia, which has conservative religious views, the right to freedom of expression often clashes with dominant religious norms. This research uses the perspective of students to explore their understanding of GNC issues, which can reflect the level of inclusivity and diversity in the campus community. Based on the 1945 Constitution article 28E paragraph 2 which guarantees freedom of opinion, this study examines whether the freedom of gender expression non-conformities is acceptable or actually causes conflict, especially in relation to the protection of human rights (HAM) and existing religious views. The results of this study are expected to provide insight into how the younger generation views gender issues that are not limited to traditional norms, as well as the role of higher education in shaping this perspective.